The Role of Kinesthetic Movements in Jolly Phonics Instruction: Supporting Letter Sound Awareness among Toddlers - Agnessia, Ni Putu Dian; Ni Made Diana Erfiani; Yohanes Octovianus Lesu Awololon (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study investigated the role of kinesthetic movements in supporting letter-sound awareness among toddlers aged 2 years at a child care center in Canggu, Bali. A qualitative descriptive design was employed to examine how movement-based phonics instruction facilitated early literacy development. Data were collected through classroom observations, field notes, and a Likert-scale observation checklist during eight instructional sessions involving 15 children. The analysis focused on four indicators: imitating the kinesthetic gesture, producing the letter sound, responding to a heard letter sound, and identifying the corresponding letter. The study was guided by the principles of structured teacher support and multimodal learning, which emphasize integrating verbal and physical experiences in early learning. Data were analyzed using an interactive qualitative approach involving data reduction, data display, and conclusion drawing. The findings revealed a gradual improvement in children’s recognition of the five-target letter sounds across the instructional sessions. Letter sounds accompanied by more distinctive movements were acquired more quickly than those accompanied by less noticeable movements. The results suggested that kinesthetic movements effectively supported letter-sound awareness and contributed to early literacy development among toddlers.